Managing Innovation in Boarding Schools to Develop Qur’anic Character in Public Senior High Schools - Elfiana, Reni; Bahrun, Bahrun; Ismail, Ismail (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to examine the management strategies, implementation processes, and challenges of character education in boarding programs at two public high schools. Although national education policy emphasizes character development, empirical evidence on how such programs are planned, implemented, and evaluated in school settings remains limited. This study employed a qualitative approach, with data collected through interviews, observation, and documentation. Data were analyzed using the Miles and Huberman interactive model. The results indicate that both schools systematically integrate character values into the curriculum, daily routines in the boarding school, and extracurricular activities through structured planning, implementation, and evaluation. However, significant challenges remain, such as the negative influence of mass media, inadequate facilities and infrastructure, low student motivation, and limited parental involvement. To address these challenges, the schools have implemented measures such as strengthening teacher leadership and capacity, improving facilities, developing extracurricular activities focused on character building, and increasing parental involvement through workshops and community programs. This study contributes to the theory and practice of character education in boarding schools by emphasizing the importance of context-responsive management strategies, strong stakeholder collaboration, and ongoing monitoring and evaluation.